Comparison of preeclampsia and fetal growth restriction screenings at first trimester in a high-risk population (2021)
Aim To compare the sensitivity and specificity of screening for preeclampsia and FGR including maternal characteristics, mean arterial blood pressure and uterine artery pulsatility index and the combined screening, which adds biochemical markers, such as placental growth factor (PlGF) and pregnancy‐associated plasma protein‐A (PAPP‐A), in a sample of high risk population for hypertensive disorders. Methods This is a prospective study with 527 singleton pregnancies at 11–14 weeks of gestation. Maternal characteristics, biochemical and biophysical markers were studied to determine the development of preeclampsia and FGR by using receiver operating characteristic curves. Results For preeclampsia, screening, including sociodemographic data plus biophysical markers, had a sensitivity and specificity of 70.3% (CI% 64.3–75.2) and 93.8% (CI% 90.9–96.8), respectively. Combined screening, which includes sociodemographic data, biophysical (mean blood pressure and uterine artery pulsatility index) and biochemical markers (PlGF and PAPP‐A), increased sensitivity and specificity up to 85.5% (CI% 80.2–90.3) and 96.3% (CI% 91.4–98.9), respectively. For FGR, sociodemographic data plus biophysical markers had a sensitivity and specificity of 57.8% (CI% 50.1–63.4) and 80.1% (CI% 74.3–85.9), respectively. Combined screening increased sensitivity and specificity up to 67.2% (CI% 52.1–71.3) and 82.7% (CI% 75.2–90.1), respectively. Conclusion Combined screening for preeclampsia and FGR at 11 to 14 weeks of gestation, which includes maternal characteristics, mean blood pressure, uterine artery pulsatility index, PAPP‐A and PlGF, has higher sensitivity and specificity than other screening options. Therefore, considering all these variables during screening is recommended for a superior opportunity of identifying pregnant women in risk for preeclampsia and FGR, especially in a high‐risk population.